Muscone suppresses inflammation and senescence of nucleus pulposus via p53 signalling during intervertebral disc degeneration - Ruizhe Wang; Zifan Zhang; Jinhai Xu; Ye Tian; Guoqing Wen; Huajian Zhong; Leixin Wei; Huiqiao Wu; Xiaolong Shen; Yu Chen; Peng Cao; Yang Liu; et al. (Scientific Reports)
Abstract Intervertebral disc degeneration (IDD) is a major cause of chronic low back pain, the mechanism of which is still unclear. Inflammation-induced extracellular matrix metabolism (ECM) dysregulation in the nucleus pulposus (NP) and NP cell senescence are known to be the key causes of IDD. However, few drugs can reliably alleviate ECM dysregulation and NP cell senescence. Muscone, as the key natural component of musk, is a widely applied antiapoptotic and anti-inflammatory drug. We found Muscone exerts protective effects by inhibiting the expression of ECM catabolism-related genes, cell apoptosis, the cell senescence and senescence-associated secretory phenotype (SASP) in NP cells, which is the key cellular phenotype associated with IDD. We have also shown that muscone can increase the expression of ECM anabolism-related genes and the proliferation of NP cells during inflammation. High-throughput RNA sequencing indicated that muscone protects NP cells mainly by altering the phosphorylation and expression of p53. Further validation confirmed both in vivo and in vitro that muscone could regulate ECM-related genes, cell apoptosis, cell senescence and the SASP by inhibiting p53. In summary, our findings show that muscone protects against the degeneration of nucleus pulposus cells by inhibiting p53 signaling and thus may have therapeutic value for IDD.